THE EFFECT OF USING INSTAGRAM SOCIAL MEDIA ON FOLLOWERS' INFORMATION REQUIREMENTS IN FOLLOWING ACCOUNTS @FOLKATIVE - Rina Astriani; Sendi Eka Nanda (Jurnal Sosial Humaniora dan Pendidikan, 2022)
The @folkative Instagram account is an Instagram account belonging to the Folkative Group company. Folkative itself is a well-known online media platform in Indonesia that shares a variety of up-to-date information both from within the country and abroad. This study was conducted to determine the effect of using Instagram social media on meeting the information needs of followers on the @folkative account. The approach used in this research is quantitative and the paradigm used is the positivistic paradigm. The results of this study indicate that there is an effect of using Instagram social media on meeting the information needs of followers on the @folkative account by 68.1% while the remaining 31.9% is influenced by other variables not examined in this study.